RETHINKING CLIMATE CHANGE AND NATIONAL SECURITY: IMPLICATIONS FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - AUSTEEN NDUBUISI ADIGWE (International Studies Journal)
The phenomenon of climate change is providing a melting point to the global community through its pervading and undeniable implications for life on planet earth. The overwhelming impact of this on human interface, no doubt raises concerns that cuts across creed, colour, religion, and regional calibrations. It is generally believed that change remains a constant in human affairs; and all creatures anticipate change in their negative and positive configurations. Climate change is the response of nature to the increasing intervention and interference of man in the natural ecosystem, leading to fluctuations in average global temperatures often described as global warming. The implications of this in the long run remains unpredictable but the effect of this in contemporary times is orchestrating outcomes that offers no heritage of good to all and sundry. This ranges from decreased precipitation to deforestation and desertification, the poleward shift of vegetation and its impact on animal populations, the unmitigated rise in sea levels among others. This study interrogates the concept of climate change in the light of national security with the commitment to underscore its implication for sustainable development in Nigeria. Historical materialism offered the theoretical framework for this investigation under the methodological philosophy of qualitative analysis as obtainable in social inquiry. The study unearthed the economic effects of climate change, and underscored the historical, structural and institutional factors that explains why third world countries are more susceptible to climate change. Such factors like poor and weak governance structures, endemic conflict, among others negatively exacerbate the challenge of climate change in these climes. It was on the basis of this that it interrogated the polemics of climate change to national security, and the unmitigated implications of this to sustainable development in Nigeria. It offered the blueprints on the way forward with a modest conclusion.